Anthropogenic effects on the physical and chemical properties of subtropical coastal urban soils (2012)
We investigated the effects of various anthropogenic factors on urban soil properties in subtropical, coastal Tampa, FL, USA. Specifically, we explored the influence of (i) urbanization as measured by land use, land cover, population density and years since urban development and (ii) socioeconomic conditions as reflected in household income and property values on bulk density (BD) and several key soil chemical properties. Results indicate that Tampa’s urban soils were affected to varying degrees by these factors with chemical properties being more variable than BD. Across land uses significant differences were found for Mehlich?1 (M1) extractable P, Ca and Na. A similar trend was observed for land?cover classes, although significant differences were also found for pH and M1?Cu. Soil properties had no statistically significant relationship with population density. However, time since urbanization did with M1?P and Na varying significantly across age categories. For our socioeconomic analyses, M1?K and Mg levels differed significantly by household income while pH, P, Ca and Na values differed significantly by property value. Overall, our findings indicate that despite their inherent heterogeneity, there are identifiable patterns among subtropical coastal urban soil properties. We suggest that a more thorough understanding of these patterns and their drivers is an essential first step towards developing soil management strategies aimed at maintaining environmental quality and ecosystem services in subtropical cities.